High Saturated Fat Diet Alters the Lipid Composition of Triacylglycerol and Polar Lipids in the Femur of Dam and Offspring Rats. Issue 6 (29th April 2015) - Miotto, Paula M.; Castelli, Laura M.; Amoye, Foyinsola; Ward, Wendy E.; LeBlanc, Paul J.
Abstract: Previous work has shown that dietary lipids alter femur lipid composition. Specifically, we have shown that exposure to high saturated fatty acid (SFA) diets in utero, during suckling, or post‐weaning alters femur total lipid composition, resulting in higher percent bone mass in males and females and bone mineral density (BMD) in female offspring with no effect on bone mineral outcomes in dams. Comparatively, high n‐3 polyunsaturated fatty acid (PUFA) diets increase femur polar (PL) lipid n‐3 content, which has been associated with increased bone mineral content and strength. However, the extent that PL or triacylglycerol (TAG) lipids change with high SFA diets is unknown. The current investigation examined the influence of a high SFA diet (20 % lard by weight) on femur PL and TAG lipid composition in 5‐month old female Wistar rats (fed high SFA diet from age 28 days onwards; dams) and their 19‐day old offspring (exposed to high SFA in utero and during suckling; pups). High SFA exposure resulted in increased monounsaturates and decreased n‐3 and n‐6 PUFA in the TAG fraction in both dams and pups, and higher SFA and n‐6:n‐3 ratio in dams only. The PL fraction showed decreased n‐6 PUFA in both dams and pups. The magnitude of the diet‐mediated responses, specifically TAG 18:1 and PL n‐6 PUFA, may have contributed to the previously reported altered BMD, which was supported with correlation analysis. Future research should investigate the relationship of diet‐induced changes in bone lipids on bone structure, as quantified through micro‐computed tomography.